(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
India as post-colonial country is of growing concern in the world due to several criteria such as its economic development and others despite the fact that it was colonized around two centuries by the British Empire. This dissertation examines how India changed during the colonial and the postcolonial periods in both economy and culture. The main argument of this study is that radical changes have occurred in India both economically and culturally during colonialism and after its demise.